Dampak Peristiwa Stock Split Terhadap Performa Saham Di Bursa Efek Indonesia - Muhammad Taufiq Abadi (Universitas Serang Raya, 2022)
This study aims to determine and calculate differences in the level of stock liquidity proxied by the company's trading volume activity (TVA) before and after the stock split, the next goal is to determine the difference in stock price levels before and after the announcement of the stock split, and the last is to determine changes in stock prices. the growth of the company's net profit due to the announcement of the Stock split. The variables used in this research are stock split, trading volume activity, stock price and profitability. The sample used is 27 companies that perform stock splits throughout 2019-2022. In this study, the researchers used a paired sample t-test and the influence test using multiple regression with the help of the Microsoft Excel program and the statistical package the social science (SPSS) VERSION 23.0. The results showed that the paired sample t-test on trading volume activity 7 days before and 7 days after the announcement date of the stock split showed that the stock split had a significant impact on trading volume activity. share. And the last result shows that the stock split has no effect on the company's profit growth on the Indonesian stock exchange. keyword: stock split, liquidity, and trading volume activity